PELATIHAN DAN PENDAMPINGAN PENGGUNAAN APLIKASI E-MONEV PADA DINAS BAPPEDA KABUPATEN LOMBOK TENGAH - Indah Cahyanti, Riska; Fadli, Sofiansyah; Fahmi , Hairul; Fauzi Zulkarnain, Mohammad; saikin, Saikin (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2023)
The general reality that occurred in the budget realization and performance reporting system in Central Lombok Regency before E-Monev was put into practice was that the process was very slow, complicated, and very convoluted, not infrequently even very tiring. Reports that should be done in one day may take one week, two weeks or even one month. To expedite the reporting or monitoring process, Bureaucratic Reform (RB) efforts were made by developing online-based systems and applications called E-Monev. E-Monev is an instrument for monitoring, evaluating and controlling budget realization and performance which is used to collect data and information on monitoring results. This web-based application makes it very easy for employees to record budget realization and performance while in the office, such as filling in and changing work plans, filling out sub-activities, and there are other forms provided for reporting according to their respective duties and roles. What is expected from this web-based application is that employees can use the application as well as possible and can facilitate work and help company performance, especially in the field of Human Resources, to be faster, better and more practical.